Genetic Contribution to Initial and Progressive Alcohol Intake Among Recombinant Inbred Strains of Mice - Mulligan, Megan K.; Zhao, Wenyuan; Dickerson, Morgan; Arends, Danny; Prins, Pjotr; Cavigelli, Sonia A.; Terenina, Elena; Mormede, Pierre; Lu, Lu; Jones, Byron C. (Frontiers in Genetics, 2018)
We profiled individual differences in alcohol consumption upon initial exposure and during five weeks of voluntary alcohol intake in female mice from 39 BXD recombinant inbred strains using the drinking in the dark (DID) method. In this paradigm, a single bottle of 20% (v/v) alcohol was presented as the sole liquid source for 2 or 4h starting three hours into the dark cycle. For three consecutive days mice had access to alcohol for 2h followed by a fourth day of 4h access and three intervening days where alcohol was not offered. We followed this regime for five weeks. For most strains, 2 or 4h alcohol intake increased over the 5-week period, with some strains demonstrating greatly increased intake. There was considerable and heritable genetic variation in alcohol consumption upon initial early and sustained weekly exposure. Two different mapping algorithms were used to identify QTLs associated with alcohol intake and only QTLs detected by both methods were considered further. Multiple suggestive QTLs for alcohol intake on chromosomes (Chrs) 2, 6, and 12 were identified for the first 4h exposure. Suggestive QTLs for sustained intake during later weeks were identified on Chrs 4 and 8. Thirty high priority candidate genes, including Entpd2, Per3, and Fto were nominated for early and sustained alcohol intake QTLs. In addition, a suggestive QTL on Chr 15 was detected for change in 2h alcohol intake over the duration of the study and Adcy8 was identified as a strong candidate gene. Bioinformatic analyses revealed that early and sustained alcohol intake is likely driven by genes and pathways involved in signaling, and/or immune and metabolic function, while a combination of epigenetic factors related to alcohol experience and genetic factors likely drives progressive alcohol intake.